The bazaar in the Islamic city : design, culture, and history - Gharipour, Mohammad (American University in Cairo Press, 2012)
The Middle Eastern bazaar is much more than a context for commerce: the studies in this book illustrate that markets, regardless of their location, scale, and permanency, have also played important cultural roles within their societies, reflecting historical evolution, industrial development, social and political conditions, urban morphology, and architectural functions. This interdisciplinary volume explores the dynamics of the bazaar with a number of case studies from Cairo, Damascus, Aleppo, Nablus, Bursa, Istanbul, Sana'a, Kabul, Tehran, and Yazd.